COVID-19 Pandemic, Dividend Policy, and Stock Market Reaction: Evidence from the Manufacturing Companies in Indonesia - Powell Gian Hartono; Muhammad Yaasiin Raya (University of Merdeka Malang, 2022)
This study aimed to examine the impact of the COVID-19 crisis on the dividend policy of Indonesia’s manufacturing companies and the stock market reaction to this corporate action in 2020. The purposive sampling technique was used to select 87 manufacturing companies to examine the impact of the crisis on dividend policy from 2014 to 2020, while the market reaction was tested on 42 companies. Data were analyzed using the dynamic panel data regression with the SYS-GMM estimation method, as well as the one sample T-test and the Wilcoxon sign-ranked tests. The findings showed that Indonesia’s manufacturing companies formulated a positive dividend policy during the COVID-19 pandemic. The stock market reaction to this corporate action was weak, meaning it became sluggish during a crisis. These results indicate that the effort to signal the market positively was ineffective. Therefore, companies must formulate corporate actions or other managerial policies to reduce capital market sluggishness in crisis. They should also implement an optimal dividend policy to increase their value to contribute to the Indonesian economy, specifically in crisis conditions, such as the COVID-19 pandemic.